2013
DOI: 10.1136/bmjopen-2013-002593
|View full text |Cite
|
Sign up to set email alerts
|

Parental modelling, media equipment and screen-viewing among young children: cross-sectional study

Abstract: ObjectiveTo examine whether parental screen-viewing, parental attitudes or access to media equipment were associated with the screen-viewing of 6-year-old to 8-year-old children.DesignCross-sectional survey.SettingOnline survey.Main outcomeParental report of the number of hours per weekday that they and, separately, their 6-year-old to 8-year-old child spent watching TV, using a games console, a smart-phone and multiscreen viewing. Parental screen-viewing, parental attitudes and pieces of media equipment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
(27 reference statements)
3
36
0
Order By: Relevance
“…Moreover, many mothers participating in the present study reported lack of support from their husbands in their efforts to set up and enforce rules to limit ST. Previous studies suggest that mothers and fathers have different parental influences on their children's ST behaviors and both should be included in interventions [61][62][63]. Our findings, combined with that of prior research, suggest that future parenting interventions designed for Brazilian immigrant families should be family-focused and involve other family members, including fathers.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, many mothers participating in the present study reported lack of support from their husbands in their efforts to set up and enforce rules to limit ST. Previous studies suggest that mothers and fathers have different parental influences on their children's ST behaviors and both should be included in interventions [61][62][63]. Our findings, combined with that of prior research, suggest that future parenting interventions designed for Brazilian immigrant families should be family-focused and involve other family members, including fathers.…”
Section: Discussionsupporting
confidence: 65%
“…Previous research suggests that parental monitoring, especially maternal monitoring, of ST is associated with less ST for children [56,62]. Similarly, prior evidence suggests that setting limits and having ST rules is associated with children's ST [34,56,62,63]. Nevertheless, several mothers participating in this study acknowledged that it can be challenging to sustain and enforce parenting practices to manage their children's ST, especially given the availability of multiple screen devices in the house.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…So you have to be active yourself'— F05 . Because several studies have found significant associations between parental modelling and child nutrition, physical activity, and screen time behaviours (Jago et al, ; Natale et al, ), it is likely that parents who are active and model healthy lifestyles choices will have children who make similar choices. Prior research has identified that parents engaging in physical activity in the presence of their children experience the barrier that they find it difficult to reach the workout intensity required for personal benefit, due to factors such as attending to the child (Hamilton & White, ).…”
Section: Resultsmentioning
confidence: 99%
“…While the responsibility to model physical activity, and be active with one's child, emerged as an important parental role, it was indicated that due to busy lifestyles and competing demands on parents' time, doing so is not always practical. Because parental modelling has been found to predict children's health behaviours (Jago et al, ; Natale et al, ), it is likely that interventions effective in promoting active lifestyles in parents (such as those identified by Hamilton & White, ) would have a subsequent effect of increasing physical activity‐related behaviours in their children. Promoting integrative activities (Hamilton & White, ), where parents can be active alongside their child, may be a particularly useful approach for promoting child physical activity‐related behaviours in a time‐efficient manner.…”
Section: Resultsmentioning
confidence: 99%